Ranitidine And Omeprazole Effect On Serum Phosphorus In Hemodidlysis Patients - D. ELBOHY,; M. EL-HAMMAMSY,; M.EL-SHARKAWY, (International Journal of Pharma and Bio Sciences, 2011)
Hyperphosphatemia induces extraskeletal calcification of soft tissue, a link found between gastric hyperacidity and hyperphosphatemia in dialysis patients. Patientsts categorized into 3 groups viz., Group I (38 Patients) control group, Group II (39 Patients) CaCo3 with Ranitidine 150 mg and Group III (31 subjects) same dose calcium carbonate with Omeprazole 20 mg. Blood samples were collected monthly during hemodialysis sessions.Group II showed increase in serum phosphorus at 6th months with increase in calcium-phosphorus biproduct, decreased serum calcium. Group III showed no significant change in serum calcium, phosphorus, Parathyroid hormone and calcium-phosphorus biproduct value. Co-administration of Ranitidine with calcium carbonate may aggravate hyperphosphatemia increasing the incidence of complications. Co-administration of Omeprazole with calcium carbonate may have a beneficial role in minimizing those complications in those patients.